The internationalization theory and Malaysian small medium enterprises (SMEs) - Nik Abdullah, Nik Ab. Halim; Mohd Zain, Shahrul Nizam (International Association of Computer Science and Information Technology Press (IACSIT Press), 2011)
Reduction in trade barriers and development in information and communication technology provide the opportunity for small and medium enterprises (SMEs) to expand their business into foreign market, even on the first day of its establishment.Such circumstances have lead into a debate among internationalization researchers on which theory effectively explain the firm’s internationalization process and whether the older theories are not relevant anymore these days.Therefore, the objective of this paper is to look at the internationalization process of Malaysian SMEs and how it fits the internationalization theories. Discussions are based on the related theories of internationalization namely the Uppsala Model, Network Approach and International New Venture or Born global.This paper also presents a descriptive analysis on the level of internationalization among Malaysian SMEs, reason for internationalization, the mode of entry used, and the reason for non-internationalization among firms that have no international activities.Data were collected through self-administered questionnaire and a total of 250 responds were received.Findings indicate that all three theories are still applicable as not all SMEs that internationalized are born global in nature.Exporting was the most used mode of entry and increasing profit was the main reason for internationalization.Potential difficulties and uncertainties in making profit appear to be the major reason for non-internationalization.Discussions of the findings, significance of the study and direction for future research are then discussed.